2019
DOI: 10.1007/s00234-019-02218-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic assessment of foetal brain malformations with intra-uterine MRI versus perinatal post-mortem MRI

Abstract: Purpose To evaluate differences in diagnostic yield of intra-uterine foetal (iuMR) and post-mortem MRI (PMMR) for complex brain malformations, using autopsy as the reference standard. Methods In this retrospective, multicentre study spanning 2 years, we reviewed 13 terminated singleton pregnancies with a prenatal ultrasound finding of complex foetal cerebral abnormalities, referred for both iuMR and PMMR. The iuMR and PMMR studies of the brain were reported independentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…5) The value of an international program to help support countries and demonstrate the value of paediatric postmortem MRI to governments and insurance companies. 6) One centre has shown that paediatric postmortem MRI is not as accurate as intrauterine foetal MRI for central nervous system cases [17], a finding supported by another study [18]. Consequently, the centre is now using intrauterine foetal MRI as a first step in postmortem investigations when there is an intention to terminate the pregnancy due to a foetal cranial abnormality.…”
Section: Imaging Protocols (Table 2)mentioning
confidence: 99%
“…5) The value of an international program to help support countries and demonstrate the value of paediatric postmortem MRI to governments and insurance companies. 6) One centre has shown that paediatric postmortem MRI is not as accurate as intrauterine foetal MRI for central nervous system cases [17], a finding supported by another study [18]. Consequently, the centre is now using intrauterine foetal MRI as a first step in postmortem investigations when there is an intention to terminate the pregnancy due to a foetal cranial abnormality.…”
Section: Imaging Protocols (Table 2)mentioning
confidence: 99%
“…There is now also evidence that where a fetal brain malformation is suspected and termination of pregnancy is to be sought that intrauterine fetal MRI may be even more accurate than the PMMR . However, where an intrauterine death or stillbirth has occurred prior to the possibility for performing an intrauterine fetal MRI, then PMMR would be the next best option.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CNS abnormalities is 0.14-0.16% in live births and reaches 3-6% in stillbirths [1]. They are the most common reason for pregnancy terminations owing to their poor longterm outcomes [2].…”
Section: Introductionmentioning
confidence: 99%